2021
DOI: 10.3389/fnut.2021.740286
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Carotenoid Cleavage Dioxygenase 4 Homoeologs in Carotenoid Accumulation and Plant Growth in Tetraploid Wheat

Abstract: The dietary needs of humans for provitamin A carotenoids arise from their inability to synthesize vitamin A de novo. To improve the status of this essential micronutrient, special attention has been given to biofortification of staple foods, such as wheat grains, which are consumed in large quantities but contain low levels of provitamin A carotenoids. However, there remains an unclear contribution of metabolic genes and homoeologs to the turnover of carotenoids in wheat grains. To better understand carotenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, several genes involved in glutathione (Yamazaki et al 2019 ), carotenoid (Yu and Tian. 2021 ), ascorbate (Munir et al 2020 ), unsaturated fatty acid biosynthesis (Xue et al 2020 ) and phenylalanine metabolism (Xu and Zhang. 2020 ) were significantly activated in the transgenic strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several genes involved in glutathione (Yamazaki et al 2019 ), carotenoid (Yu and Tian. 2021 ), ascorbate (Munir et al 2020 ), unsaturated fatty acid biosynthesis (Xue et al 2020 ) and phenylalanine metabolism (Xu and Zhang. 2020 ) were significantly activated in the transgenic strains.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 ), ascorbate (Munir et al 2020 ), unsaturated fatty acid biosynthesis (Xue et al 2020 ) and phenylalanine metabolism (Xu and Zhang. 2020 ) were significantly activated in the transgenic strains. These results indicated that TvHSP70 over-experssion triggered enzymatic and non-enzymatic anti-oxidant defence mechanisms in Tv-1511 to cope with adverse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, increasing efforts have been made in the basic and applied research areas to understand the genetic basis of wheat quality, especially the nutritional quality traits, and to genetically improve these traits 4 , 5 . For example, several key enzymes in the carotenoid biosynthetic pathway have been functionally studied, including β-hydroxylase (HYD) 6 , lycopene epsilon cyclase (LCYε) 7 , carotenoid cleavage dioxygenases (CCD) 8 and aldehyde oxidase (AO) 9 , 10 , and transgenic wheat lines or mutant lines have been investigated to discover their effects on biofortification of β-carotene in wheat 11 15 . More recently, owing to the technological advances in metabolomics ( e.g ., the widely targeted metabolomics based on ultra-performance liquid chromatography- electrospray ionization-tandem mass spectrometry (UPLC-ESI-MS/MS) 16 ), large-scale identification and quantification of phytochemicals in wheat seeds has become possible.…”
Section: Background and Summarymentioning
confidence: 99%